Isamaa Ilu . Beauty of the Fatherland - Kilmi, Jaak; Maimik, Andres (Estonia, 2001)
Verzio FF Duration: 00:56:00 The film focuses on two protagonists whose views seem at first to embody opposing values and viewpoints: ex-Miss Estonia Tiina Jantson runs beauty contests, while Anne Eenpalu promotes traditional family values as leader of the Girl Scout troupe known as Home Daughters. Each has her own history: Tiina was a supermodel in the Soviet Union, Anne is a granddaughter of Kaarel Eenpalu, one of the presidents of the pre-war Republic of Estonia. Yet the main characters have more in common than might first appear. They are brought together by their very conservative notion about the role of women in society. Both claim to help the talents of young girls unfold, both project their own ideas and desires on them.